1999
DOI: 10.1007/s002619900449
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal malignant mesenchymoma: imaging findings in five cases

Abstract: The radiologic findings of large expansile heterogeneous masses in the retroperitoneum, especially with massive calcifications, were considered to be typical of malignant mesenchymomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…The massive calcification we found corresponded to an osteosarcomatous component, while the non-calcified enhancing nodules were, respectively, consistent with leiomyosarcoma, liposarcoma, and fibrosarcoma. A well-differentiated liposarcomatous component can have a fatty component (5), though in our case none was apparent at CT. The composition of a malignant mesenchymoma - whether or not it contains calcification or ossification, a fatty component, or necrotic soft tissue - seems to determine its radiological features.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…The massive calcification we found corresponded to an osteosarcomatous component, while the non-calcified enhancing nodules were, respectively, consistent with leiomyosarcoma, liposarcoma, and fibrosarcoma. A well-differentiated liposarcomatous component can have a fatty component (5), though in our case none was apparent at CT. The composition of a malignant mesenchymoma - whether or not it contains calcification or ossification, a fatty component, or necrotic soft tissue - seems to determine its radiological features.…”
Section: Discussioncontrasting
confidence: 63%
“…Although none were common to all the cases they described, Suzuki et al (5) suggested that the typical findings of malignant mesenchymoma were large tumor size, a sharp margin, heterogeneous make-up, and massive calcification. The tumor in our case was also a huge heterogeneous mass with massive intratumorous calcification, but a feature different from those previously noted was also present.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The radiologic findings of well-circumscribed and heterogeneous mass which, including osteosarcomatous components, were considered to be MMs. [ 8 ] In our case, tumor was a homogeneous mass and without calcification. It was hard to determine malignant character although the biopsy was done before operation.…”
Section: Discussionmentioning
confidence: 61%
“…25 It has been postulated that this tumor could arise from primitive and uncommitted mesenchymal cells that differentiate along multiple cell lines. 8,16 Various authors have postulated a relationship between trauma and scar formation in the development of mesenchymoma in humans 24 and dogs.…”
mentioning
confidence: 99%